ANALYSIS OF THE RELATIONSHIP BETWEEN AGE, GENDER, AND LENGTH OF EMPLOYMENT WITH WORK-RELATED STRESS AMONG NURSES - Hapsari, Restiana Kartika Mantasti; Noor, Ihya Hazairin; Nisa, Mufatihatul Aziza (Universitas Kusuma Husada Surakarta, 2025)
Background: Work-related stress is a common issue among nurses and can affect their performance, quality of care, and psychological well-being. This study aimed to analyze the relationship between age, gender, and length of service with work-related stress levels among nurses at a hospital in Banjarbaru City.Methods: A quantitative approach with a cross-sectional design was used. The sample consisted of 120 nurses at a hospital in Banjarbaru City selected through proportional stratified random sampling. Data were collected using a demographic questionnaire and the Perceived Stress Scale (PSS), which has been validated in previous studies with a Cronbach’s alpha of 0.82. Data were analysed using the Chi-Square test with a significance level of 0.05.Results: The results showed no significant relationship between age (p=0.298), gender (p=0.397), and length of service (p=0.581) and the level of work-related stress. However, descriptive results indicated a higher proportion of stress among nurses who were female, younger, and had longer work experience.Conclusion: It is recommended that hospital management focus more on workload, work environment, and psychosocial support rather than individual demographic factors in managing work stress.